2012
DOI: 10.1017/s0950268812000969
|View full text |Cite
|
Sign up to set email alerts
|

Social contact patterns and leprosy disease: a case-control study in Bangladesh

Abstract: Socioeconomic and culturally defined social contact patterns are expected to be an important determinant in the continuing transmission of Mycobacterium leprae in leprosy-endemic areas. In a case-control study in two districts in Bangladesh, we assessed the association between social contact patterns and the risk of acquiring clinical leprosy. Social contacts of 90 recently diagnosed patients were compared to those of 199 controls. Leprosy was associated with a more intensive social contact pattern in the home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
19
2
5
Order By: Relevance
“…Higher leprosy rates among household contacts of patients with multibacillary leprosy might be explained by the exposure to relatively higher bacillary load. 20,21 Similar to our findings, previous research has reported higher odds of leprosy detection among contacts who are older 5,22,23 and male. 2 In this study, we found lower leprosy detection among contacts with lower educational levels.…”
Section: Discussionsupporting
confidence: 91%
“…Higher leprosy rates among household contacts of patients with multibacillary leprosy might be explained by the exposure to relatively higher bacillary load. 20,21 Similar to our findings, previous research has reported higher odds of leprosy detection among contacts who are older 5,22,23 and male. 2 In this study, we found lower leprosy detection among contacts with lower educational levels.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that, in addition to household contacts, people living in the vicinity of a leprosy case and their social contacts have a higher risk of infection [18], [26], [37]. In fact, because M. leprae is highly infective but has a low pathogenicity, most people who harbor a subclinical infection will never develop clinical signs and symptoms of leprosy; indeed, only about 10% of all infected individuals eventually develop leprosy symptoms [38].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of performing periodic surveillance among household contacts and including different classes of social and neighboring contacts has been highlighted by several authors [33], [37], [48]. Bakker and colleagues [18] observed increased subclinical infection for contact groups living ≤75 meters of anti-PGL-I-positive leprosy patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted in Gujarat India stated that out of 250 respondents of lepers, 8.30% of them had a contact history of family and environment (Thakkar & Patel, 2014). Research conducted by Feenstra, Nahar, Pahan, Oskam, & Richardus (2013) showed that household contact has an influence with clinical leprosy with an OR value of 1.09. Contacts in the nearest environment are also associated with clinical leprosy with an OR value of 1.07.…”
Section: Influence Of Risk Factors On New Leprosy Casesmentioning
confidence: 99%
“…The possibility of transmission of the disease still exists even though the leper has received treatment. Leprosy is associated with close family contact and contact with leprosy in the social environment, which identifies contact exposure as the main determinant of leprosy transmission (Feenstra, Nahar, Pahan, Oskam, & Richardus, 2013). The possibility of transmission through the respiratory tract is increasing where the respiratory tract is one of the portals of exit Mycobacterium leprae.…”
Section: Influence Of Risk Factors On New Leprosy Casesmentioning
confidence: 99%